Influencia del fósforo sobre las leguminosas naturales en el potrero tropical - Jiménez R, E.; Alba, Jorge de; Muñoz, H. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Total green and dry matter yield of grasses and legumes was studied for a year in tropical pastures following the application of two levels of superfosfate. The yield of legumes benefited from the phosphate applications. But even though this increase was statistically significant, the total increase in dry matter contributed by the native legumes (mostly of the genus Desmodium) was much too low to be of economic significance to cattle feeding. The grass yield or its protein content was not benefitted by the phosphate applications.